2017
DOI: 10.1002/aqc.2789
|View full text |Cite
|
Sign up to set email alerts
|

A century of fishery data documenting the collapse of smooth‐hounds (Mustelus spp.) in the Mediterranean Sea

Abstract: Conservation and management of shark populations is increasingly becoming important in many marine regions, since there is a growing body of evidence showing that several species are threatened and continuing to decline because of unregulated fishing. Quantifying the extent of sharks' decline, the risk of species extinction, and the consequences for marine ecosystems have been challenging and controversial, mostly due to data limitations. In this study, more than one century of multiple‐sources of bibliographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 48 publications
9
56
0
Order By: Relevance
“…The case was also reported for Squatina squatina (Linnaeus, 1758) [65]. Recent analysis of the frequency of occurrence of smooth-hounds in fishery catch data showed that the species have declined by 80-90% since the beginning of last century to almost disappear in a large part of their original distributional range during the 1980s and 1990s [66]. landing for elasmobranchs between 1997 and 2004 decreased 77% compared with the previous years .…”
Section: Impact Of Fisheriesmentioning
confidence: 63%
“…The case was also reported for Squatina squatina (Linnaeus, 1758) [65]. Recent analysis of the frequency of occurrence of smooth-hounds in fishery catch data showed that the species have declined by 80-90% since the beginning of last century to almost disappear in a large part of their original distributional range during the 1980s and 1990s [66]. landing for elasmobranchs between 1997 and 2004 decreased 77% compared with the previous years .…”
Section: Impact Of Fisheriesmentioning
confidence: 63%
“…However, no effective management measures against the overexploitation of many commercial species have been successfully implemented or enforced (Vasilakopoulos et al 2014, Osio et al 2015. In addition, data on the stock status of sharks and rays remain poor or non-existent (Polidoro et al 2008, Worm et al 2013, Colloca et al 2017.…”
Section: Variabilidad Espacial De Chondrichthyes En El Norte Del Medimentioning
confidence: 99%
“…For example, pelagic sharks declined by more than 95% during the last century (Ferretti et al, 2008), whilst demersal sharks, such as smooth-hounds (Mustelus spp. ), disappeared from most of the West Mediterranean in '70s and '80s (Massutí, 1971;Aldebert, 1997;Maynou et al, 2011;Ligas et al, 2013;Fortibuoni et al, 2016;Colloca et al, 2017).…”
Section: Impact Of Fishing On Commercial Stocks and By-catch Speciesmentioning
confidence: 99%